2021
DOI: 10.1111/cts.12958
|View full text |Cite
|
Sign up to set email alerts
|

Effect of meal timing on pharmacokinetics and pharmacodynamics of tegoprazan in healthy male volunteers

Abstract: Tegoprazan, a novel potassium‐competitive acid blocker, is used to treat acid‐related diseases. However, there is no information on the pharmacokinetic (PK) and pharmacodynamic (PD) profiles of the marketed dosage of tegoprazan under various meal timings in a fed and fasted state. The study aimed to assess the effect of meal timing on PKs and PDs of tegoprazan 50 mg after a single administration in healthy male subjects. An open‐label, single‐dose, three‐treatment, three‐period crossover study was conducted. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 18 publications
(18 reference statements)
2
23
0
Order By: Relevance
“…For example, the predicted exposure indices (i.e., C max and AUC) for single or repeated administration of tegoprazan were consistent with the results reported in previous clinical studies, satisfying the 2-fold criteria that is commonly used in IVIVE prediction [ 16 ]. The predicted range of time to reach C max was also comparable with the observed range in each trial [ 2 , 3 , 4 , 12 , 23 ]. In addition, the mean apparent clearance (i.e., AUC/dose) was predicted to be 17.5 L/h when tegoprazan was administered alone and decreased to 6.4 L/h by the co-administration of clarithromycin, which is similar to the results of the DDI study between tegoprazan and clarithromycin (17.7 L/h and 6.6 L/h, respectively) [ 4 ].…”
Section: Discussionsupporting
confidence: 69%
See 4 more Smart Citations
“…For example, the predicted exposure indices (i.e., C max and AUC) for single or repeated administration of tegoprazan were consistent with the results reported in previous clinical studies, satisfying the 2-fold criteria that is commonly used in IVIVE prediction [ 16 ]. The predicted range of time to reach C max was also comparable with the observed range in each trial [ 2 , 3 , 4 , 12 , 23 ]. In addition, the mean apparent clearance (i.e., AUC/dose) was predicted to be 17.5 L/h when tegoprazan was administered alone and decreased to 6.4 L/h by the co-administration of clarithromycin, which is similar to the results of the DDI study between tegoprazan and clarithromycin (17.7 L/h and 6.6 L/h, respectively) [ 4 ].…”
Section: Discussionsupporting
confidence: 69%
“…A possible reason for the decrease in C max after multiple doses is pH-dependent change in the absorption of tegoprazan, that is, the C max of tegoprazan might be reduced after multiple administrations due to augmented gastric pH caused by tegoprazan itself. In previous studies, when tegoprazan was administered with food, a decreased C max was observed with a delayed time to reach C max , which was explained by an increase in gastric pH as food dilutes the H + concentration in the stomach [ 12 , 28 ]. Because pH-dependent absorption was not reflected in the PBPK model, the difference between the observed and predicted C max might have occurred.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations